2005
DOI: 10.1029/2005gl024629
|View full text |Cite
|
Sign up to set email alerts
|

Lightning sferics and stroke‐delayed pulses measured in the stratosphere: Implications for mesospheric currents

Abstract: [1] During the Brazil Sprite Balloon Campaign 2002 -03, the vector ELF to VLF (25 Hz -8 kHz) electric and magnetic fields driven by cloud-to-ground (CG) lightning strokes at horizontal distances of 75 -600 km were measured at altitudes of 30-35 km. Electric field changes were measured for each of the 2467 CG strokes detected by the Brazilian Integrated Lightning Network. ELF pulses that occur 4 -12 ms after the retarded time of the lightning sferic, which have been previously attributed to sprites, were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In light of this tight time correlation, the absence of these pulses except at sprite times, and the theoretical analysis showing that such pulses are expected if sprites modify the local electric conductivity of the atmosphere [ Pasko et al , 1998], it is generally thought that such pulses are evidence of sprite current flowing in a small subset (around 10%) of sprites [ Cummer , 2003]. Balloon measurements of the occurrence of this class of pulse are consistent with ground measurements [ Thomas et al , 2005]. This evidence, however, is still circumstantial, and there is a well‐known lightning process, the M‐component [ Rakov and Uman , 2003, p. 176], that radiates in a similar manner.…”
Section: Introductionmentioning
confidence: 72%
“…In light of this tight time correlation, the absence of these pulses except at sprite times, and the theoretical analysis showing that such pulses are expected if sprites modify the local electric conductivity of the atmosphere [ Pasko et al , 1998], it is generally thought that such pulses are evidence of sprite current flowing in a small subset (around 10%) of sprites [ Cummer , 2003]. Balloon measurements of the occurrence of this class of pulse are consistent with ground measurements [ Thomas et al , 2005]. This evidence, however, is still circumstantial, and there is a well‐known lightning process, the M‐component [ Rakov and Uman , 2003, p. 176], that radiates in a similar manner.…”
Section: Introductionmentioning
confidence: 72%
“…Only nearby in situ measurements can determine if the magnitudes and relaxation times of the nearby lightning‐driven quasi‐electrostatic fields (QSF) and electromagnetic pulses (EMPs) above thunderstorms are sufficient for TLE production and growth. Recent studies have reported lightning‐driven QSFs and EMPs in the stratosphere at about 35 km altitude [ Holzworth et al , 2005; Thomas et al , 2005a, 2005b]. We present, for the first time, in situ measurements in the upper mesosphere and lower ionosphere that have been analyzed to specifically address TLE production.…”
Section: Introductionmentioning
confidence: 99%